The pragmatist turn : religion, the Enlightenment, and the formation of American literature - Gunn, Giles B. (Studies in religion and culture (Charlottesville, Va.), 2017)
In The Pragmatist Turn, renowned scholar Giles Gunn offers a new critical history on the ways in which seventeenth-century religion and the eighteenth-century Enlightenment influenced the formation of the American literary canon. Engaging with the work of authors ranging from Melville and Douglass to Dickinson and Morrison, he reveals the roots of a pragmatist consciousness at the heart of American culture. -- Back cover.